2008
DOI: 10.1111/j.1423-0410.2007.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

An active haemovigilance programme characterizing the safety profile of 7437 platelet transfusions prepared with amotosalen photochemical treatment

Abstract: Routine transfusion of PCT-PLT is well-tolerated in a wide range of patients. ATRs related to PCT-PLT transfusion were infrequent and most were of mild severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 17 publications
(25 reference statements)
6
96
0
2
Order By: Relevance
“…However, we did not detect any trends to indicate that pathogen inactivation of PC affected the frequency of ALI and did detect a significant increase in ventilator-free days among recipients of PC treated with pathogen inactivation during the period of transfusion support. This finding requires confirmation via subsequent prospective clinical trials or large-scale active hemovigilance studies 22,23 before concluding pathogen inactivation of PCs can reduce the severity of concomitant ALI in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not detect any trends to indicate that pathogen inactivation of PC affected the frequency of ALI and did detect a significant increase in ventilator-free days among recipients of PC treated with pathogen inactivation during the period of transfusion support. This finding requires confirmation via subsequent prospective clinical trials or large-scale active hemovigilance studies 22,23 before concluding pathogen inactivation of PCs can reduce the severity of concomitant ALI in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…In six of eight sites, INTERCEPT was used in place of g irradiation for the prevention of TA-GVHD. 34 Both of these studies were designed to measure acute transfusion reactions, and did not address the development of TA-GVHD; however, as noted in both studies, a majority of patients received repeated transfusions of INTERCEPT plts. These two reports document the widespread practice in Europe of not irradiating plts treated with the INTERCEPT process that are transfused to immunosuppressed patients.…”
Section: Interceptmentioning
confidence: 99%
“…33,34 Specifically, Osselaer et al 33 reported a prospective safety study of 5106 transfusions of plts prepared with the INTERCEPT process in five European sites, as used in routine clinical care. The INTERCEPT process was used in place of g irradiation for the prevention of TA-GVHD in all but one site.…”
Section: Interceptmentioning
confidence: 99%
“…Detailed haemovigilance and post marketing surveillance in Europe since 2003 continues to demonstrate safety and efficacy of the treated products. [54][55][56][57][58] Although high levels of inactivation have been demonstrated for a number of viruses including single-stranded RNA viruses, 38,40 the efficacy of amotosalen and UVA treatment of inactivation of high CHIKV doses had not been tested. Here, we describe the successful inactivation of high doses of CHIKV in apheresis platelet concentrates and plasma components using the amotosalen and UVA treatment process.…”
Section: Introductionmentioning
confidence: 99%